2019
DOI: 10.1002/tal.1699
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effects of torsional component of ground motions on seismic response of low‐ and mid‐rise buildings

Abstract: The torsional component of ground motion is a potential factor to excite the torsional response of buildings during earthquake, which is not explicitly considered in seismic design codes. Building codes have proposed accidental eccentricity to consider the effect of torsional component and other unpredicted factors, which may contribute to torsion in buildings. This study investigated the effects of torsional component on the buildings' responses and the adequacy of the accidental eccentricity. For this purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Finally, according to Falamarz-Sheikhabadi and Ghafory-Ashtiany [ 10 ], β = 0.05 seems to be conservative with respect to the influence of rotational ground motion for asymmetric buildings; i.e., the inherent eccentricity due to the CM/CR shift is prevalent in the structural response. Recently, Rahat Dahmardeh et al [ 110 ] concluded that torsional component can increase the structural displacement and drift ratio up to 36% and 41%, respectively, and they confirmed that = 0.05 is not sufficient for accidental eccentricity and may lead to unreliable structural responses. In all cases, the increase in displacement due to accidental torsion is greater than that recommended in the design codes.…”
Section: Experimental and Numerical Observation Of Torsionmentioning
confidence: 99%
“…Finally, according to Falamarz-Sheikhabadi and Ghafory-Ashtiany [ 10 ], β = 0.05 seems to be conservative with respect to the influence of rotational ground motion for asymmetric buildings; i.e., the inherent eccentricity due to the CM/CR shift is prevalent in the structural response. Recently, Rahat Dahmardeh et al [ 110 ] concluded that torsional component can increase the structural displacement and drift ratio up to 36% and 41%, respectively, and they confirmed that = 0.05 is not sufficient for accidental eccentricity and may lead to unreliable structural responses. In all cases, the increase in displacement due to accidental torsion is greater than that recommended in the design codes.…”
Section: Experimental and Numerical Observation Of Torsionmentioning
confidence: 99%
“…Especially, torsional irregularity effects cannot be fixed after real earthquake loads, so the subject is still hot. There are new studies on torsional provisions [15][16][17][18]. Also, Structural Equation Modeling (SEM) can be applied after static and dynamic load calculations [19].…”
Section: Introductionmentioning
confidence: 99%